PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN KOMPETENSI KEPALA SEKOLAH TERHADAP KINERJA GURU SD NEGERI DI KECAMATAN MAKASSAR KOTA MAKASSAR - Muhlis M; Abdul Saman; Widya Karmila Sari Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The principal as a leader plays a role and is responsible for organizing, monitoring, fostering, and improving the teaching and learning process. The concept of democratic leadership style and principal competence has a role in improving teacher performance. This quantitative research was conducted to determine: First: Description of the principal's democratic leadership style; Second: Description of the principal's competence; Third: Description of teacher performance; Fourth: The influence of democratic leadership style on teacher performance; Fifth: The influence of principal competence on teacher performance; Sixth: The influence of democratic leadership style and principal competence on teacher performance. Data on the description and influence of democratic leadership style, principal competence and teacher performance were collected using a questionnaire instrument with a likert scale. Data were analyzed using descriptive analysis and statistical analysis using multiple regression at a significance level of 5%. The results of the analysis show that (1) The majority of teachers gave a high rating to the principal's leadership style which reflects participation, open communication, and deliberative decision-making. This finding indicates that principals in the area have implemented democratic leadership principles consistently and effectively. (2) The principal's competence is in the very good category, with an average score of 66.44 out of a maximum of 75, or equivalent to a percentage of 88.58%. Most teachers gave a positive rating to the principal's ability to carry out his leadership role. (3) Teacher performance is in the very good category, with an average score of 64.34 out of a maximum of 74, or equivalent to a percentage of 86.94%. Most teachers are in the high score category. This indicates that teachers have good abilities in planning, implementing, and evaluating the learning process. (4) The insignificant influence of the principal's democratic leadership style on teacher performance with a significance value (> 0.05) of 0.537 with a calculated t of 0.619 < t table 1.97. (5) there is a significant influence of the principal's competence on teacher performance with a significance value (< 0.05) of 0.000 with a calculated t of 6.755 > t table 1.97. (6) there is a significant influence of the democratic leadership style and the principal's competence on teacher performance with the